Sensei's pious lie. 2 / Torikai Akane ; translation, Morgan Giles. - Torikai, Akane, 1981- (Kodansha, 2022)
"Torikai's work is a frank and nuanced examination of the emotional and practical effects of sexual violence, rendering the messy realities in gorgeously refined linework and dialogue far more naturalistic than most manga. The author veers away from blunt indictment to paint one of the most complex and fascinating psychological portraits of both rapist and victim in any medium. Very much not just for manga fans, Sensei's Pious Lie will appeal to readers of graphic novels and literary fiction in general. Blinded by our own pain, we end up hurting the very people we want to protect. Under the sway of her abuser, 24-year-old teacher Misuzu Hara must lie to herself to survive--but she's not the only one. And when she and Niizuma find themselves caught up in Kanamisa's power games, they'll all learn hard lessons about self-deception, violence, control...and maybe even love."--Publisher description.